2015
DOI: 10.1021/acscatal.5b01024
|View full text |Cite
|
Sign up to set email alerts
|

With Open Arms: Open Sites of ZrBEA Zeolite Facilitate Selective Synthesis of Butadiene from Ethanol

Abstract: Fourier transform infrared spectroscopy (FTIR) and density functional theory (DFT) calculations have been used to elucidate the nature of active sites of ZrBEA zeolite responsible for the catalytic synthesis of butadiene. We show that the content of open Zr(IV) Lewis acid sites, represented by isolated Zr atoms in tetrahedral positions of the zeolite crystalline structure connected to three -O-Si linkages and one OH-group, correlates with the catalytic activity in the process of conversion of ethanol into buta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
134
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(152 citation statements)
references
References 24 publications
12
134
0
1
Order By: Relevance
“…On the contrary, the relative amount of closed sites did not correlated with the conversion of ethanol, suggesting that they are either inactive or less active in the ETB reaction [49]. [32,49]. A direct correlation between the relative number of open Lewis acid sites and the initial rate of butadiene production was observed ( Figure 10).…”
Section: Catalysts For the One-step Processmentioning
confidence: 99%
See 3 more Smart Citations
“…On the contrary, the relative amount of closed sites did not correlated with the conversion of ethanol, suggesting that they are either inactive or less active in the ETB reaction [49]. [32,49]. A direct correlation between the relative number of open Lewis acid sites and the initial rate of butadiene production was observed ( Figure 10).…”
Section: Catalysts For the One-step Processmentioning
confidence: 99%
“…When available, this paper will also indicate the TOS at which the activity was recorded. It has been repeatedly demonstrated that the main culprit behind catalytic deactivation was the formation of coke on the catalytic surface [4,36,47,49,50]. Table 1 highlights the performances of notable catalysts for the one-step process reported in the past hundred years to provide references to the readers (catalysts 1 to 10 in Table 1), as well as the catalytic systems reviewed in this work.…”
Section: Performances and Reaction Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other heteroatoms, such as Zr, Hf, and Ti, show only one band in the 2,305-2,315 cm −1 range. Sushkevich et al (69,100) recently reported that acetonitrile preferentially binds to ZrBeta open sites and showed that CO adsorption at low temperature (∼100 K) could be used to differentiate between open and closed sites in Zr-Beta (see Figure 4d). The bands at 2,185 cm −1 and 2,176 cm −1 are assigned to CO adsorbed onto the open and closed sites, respectively.…”
Section: Indirect Detection With Probe Moleculesmentioning
confidence: 99%